A wirelessly powered low‐power digital temperature sensor. (17th January 2020) - Amin, Syed Usman; Shahbaz, Muhammad Aaquib; Jawed, Syed Arsalan; Naveed, Muhammad; Hassan, Ayesha; Mahar, Asma; Khan, Fahd; Masood, Noman; Kaleem, Danish; Warsi, Zain Hussain; Junaid, Muhammad
Summary: A wirelessly powered temperature sensor is presented in complementary metal‐oxide‐semiconductor (CMOS) 180‐nm process. The wireless power transfer (WPT) is performed using resonant magnetic coupling, and a diode‐less AC to DC conversion is achieved through a quadrature‐oscillator with native‐MOS. The quadrature‐signals are subsequently used to control the diode‐less rectifier switches. The on‐chip temperature sensor exploits the subthreshold region temperature, and the sensed temperature is converted to frequency using a ring‐oscillator, which is implemented using differential cross coupled oscillator‐based delay cells. The temperature sensor architecture also employs a temperature‐insensitive replica circuit to minimize process dependence and enhance power‐supply rejection ratio (PSRR) of the sensing process. The application‐specific integrated circuit has been designed and fabricated in 180‐nm CMOS process and has dimensions of 2 mm × 2 mm. The measurement results demonstrate that the WPT circuit generates a DC voltage of 1V with a power transfer efficiency of 85% for distances 2 to 8 mm with settling time of microseconds to milliseconds. The temperature sensor demonstrates a resolution of < ±0.6C with a sensitivity of 0.52 mV/C and 126.9 Hz/C along with PSRR of −63dB and Integral Non‐Linraity (INL) of 5% measured across six different dies. The back‐scattering communication demonstrates a −53‐dB signal at a distance of 4 mm without affecting the WPT efficiency. The total power consumption of the temperature sensor along with the integrated biases is 120 nW. Abstract : A wirelessly powered temperature sensor is presented in CMOS 180‐nm process. The measurement results show a DC voltage of 1 V with a power transfer efficiency of 85% for distances 2 ‐8 mm with temperaturesensing resolution of < ±0.6C with sensitivity 0.52 mV/C and 126.9 Hz/C along with PSRR of −63 dB and INL of 5% measured across six different dies and a total power consumption of 120 nW. The back‐scattering communication demonstrates−53‐dB signal at a distance of 4 mm.